Patient-reported systemic symptoms in women with silicone breast implants: a descriptive cohort study - Karlinde Amber Spit; Miranda Scharff; Christel JM de Blok; Frank B Niessen; Yara Bachour; Prabath W Nanayakkara (BMJ Open)
Objective An unknown portion of women with silicone breast implants (SBI) report development of systemic symptoms, recently named as ‘breast implant illness (BII)’. We aim to describe the symptoms and characteristics of women with SBI reporting these systemic symptoms and compare the clinical course of women who chose to keep their implants, to women who had their implants removed.Design Observational cohort study.Setting Specialised BII out-patient clinic at Amsterdam UMC, the Netherlands, from 2011 to 2020.Participants All women presenting to the BII clinic with SBI and systemic symptoms.Results 467 women were included for baseline analyses and 398 women for follow-up. Most frequently reported systemic symptoms at baseline included fatigue (88%), arthralgia (71%), morning stiffness (59%), myalgia (48%), cognitive impairment (33%), peripheral neurological symptoms (30%) and lymphadenopathy (22%). Furthermore, 56% reported pre-existing allergies at baseline and positive antinuclear antibodies were observed in 23%. At follow-up with a median of 3.3 years (IQR 2–4), 152 women had their implants removed on clinical grounds. Symptoms improved significantly in 65 women (43%), improved moderately in 37 women (24%), did not change in 37 women (24%) and deteriorated in 13 women (9%). Women who underwent explantation showed more improvement of their systemic symptoms compared with women who did not (OR 2.9, 95% CI 1.3 to 6.2). Additionally, women who underwent explantation within 10 years after implantation improved significantly better than women who got the implants removed after 10 years (p=0.007). Lastly, local symptoms decreased from 75% to 34% after implant removal (p<0.0001).Conclusion Most women with SBI who developed systemic symptoms experienced improvement after explantation, especially when removed within 10 years after implantation. Early recognition of the pattern of systemic symptoms in women with SBI is important and implant removal should be considered.